1981
DOI: 10.1177/002221948101400510
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Training Problems Associated with Visually and Auditorily Similar Correspondences

Abstract: Experimental figures and labels were selected that theoretically approximate the difficult discriminations encountered by young children in school (e.g., b vs d). Following pretraining on three figures, the children were randomly assigned to one of four experimental groups to investigate different methods of integrating a new, similar symbol into a set of familiar symbols. The new symbol was visually similar and its label auditorily similar to one of the three familiar symbols. The results supported Carnine's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…An area for future programmatic research is continuing formative evaluation studies, such as those conducted by Carnine (1981) and Horner and McDonald (1982). Gowin and Millman (1981) state that future evaluation research &dquo;designs are unlikely to be massive and confirmatory, but rather small and exploratory&dquo; (p. 85).…”
Section: Need For Formative Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…An area for future programmatic research is continuing formative evaluation studies, such as those conducted by Carnine (1981) and Horner and McDonald (1982). Gowin and Millman (1981) state that future evaluation research &dquo;designs are unlikely to be massive and confirmatory, but rather small and exploratory&dquo; (p. 85).…”
Section: Need For Formative Researchmentioning
confidence: 99%
“…To date, research has shown the superiority of teaching sequences that separate the introduction of visually or auditorily similar material (such as &dquo;b-d&dquo; or &dquo;p-q&dquo;) over those that attempt to introduce both members of the set at once (Carnine, 1981). White (1979) documented how training sequences designed for normal learners must be simplified and adapted for handicapped learners who are confused by too much variation in irrelevant stimulus features when learning a new geometric concept.…”
Section: Need For Formative Researchmentioning
confidence: 99%
“…More specifically, research has generated a number of procedures for selecting and sequencing positive and negative examples to facilitate concept learning. These procedures increase efficiency and effectiveness by (a) carefully sampling the full range of positive examples (Carnine, 1980a), (b) including minimally different negative examples in the teaching set (Williams & Carnine, 1981), (c) juxtaposing minimally different positive and negative examples (Granzin & Carnine, 1977), (d) creating minimal differences by transforming stimuli (Carnine, 1981;Gersten, White, Falco, & Carnine, 1982), (e) sequencing examples (Carnine, 1981;Kryzanowski & Carnine, 1980;Carnine, 1976;Carnine, 1980b;Carnine, 1980c), (f) minimizing variability in instructions (Williams & Carnine, 1981). If attention deficits interfere with the benefit that LD students derive from these procedures, specific instructional interventions may be necessary.…”
mentioning
confidence: 99%